Long-term dynamics of phenotype-dependent dispersal within a wild bird population. (8th January 2019) - Camacho, Carlos; Martínez-Padilla, Jesús; Canal, David; Potti, Jaime
Abstract: Dispersers are not a random subset of the source population, and there is considerable evidence that they differ from non-dispersers in a number of phenotypic traits. However, it is not clear whether the magnitude and direction of these differences vary over time. Between 1988 and 2016, we investigated patterns of phenotype-dependent dispersal of pied flycatchers ( Ficedula hypoleuca ) breeding in nest-boxes in their ancestral habitat (an oak forest) and a new habitat (a pine plantation) where nest-boxes were installed for pied flycatcher colonization. Natal dispersal between the oak and the pine forest is common (ca. 25% of each cohort change habitats), and this study revealed a link between male size—a major determinant of social dominance—and dispersal propensity from the pine to the oak forest. However, the extent of size-dependent dispersal decreased following the colonization of the pine forest, to the point that dispersers and non-dispersers from the 2 habitats became morphologically indistinguishable nearly 3 decades later. In addition, there was a link between local breeding densities and the distribution of large, dominant males across the 2 habitats. Overall, these results suggest that the observed patterns of size-dependent dispersal reflect a dynamic balance between dispersal motivation, determined by the density of conspecifics in the source and destination patches, and the social dominance of large over small competitors for nest cavities in densely populated areas. Future studies using a long-term dynamic approach are needed for a comprehensive understanding of the role of non-random dispersal in shaping the phenotypic trajectories of natural populations. Abstract : Dispersing animals usually differ in body size and condition from those that remain in their birthplace, which could potentially result in the emergence of morphologically distinct populations. By monitoring marked pied flycatchers over nearly 3 decades, we showed that the magnitude of the size difference between dispersers and non-dispersers varies over time, apparently according to the interplay between the attractiveness of alternative habitats and the ability of dispersers to compete for nests in preferred habitats.